2010
DOI: 10.1073/pnas.1000406107
|View full text |Cite
|
Sign up to set email alerts
|

Entropy driven self-assembly of nonamphiphilic colloidal membranes

Abstract: We demonstrate that homogeneous monodisperse rods in the presence of attractive interactions assemble into equilibrium 2D fluid-like membranes composed of a one-rod length thick monolayer of aligned rods. Unique features of our system allow us to simultaneously investigate properties of these membranes at both continuum and molecular lengthscales. Analysis of thermal fluctuations at continuum lengthscales yields the membranes' lateral compressibility and bending rigidity and demonstrates that the properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
186
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(192 citation statements)
references
References 43 publications
4
186
2
Order By: Relevance
“…We assume that membranes and p-walls formed by filamentous fd viruses are type-II smectic materials, based on the analogy with superconductors 40,41 . In other words, the coherence length x, the length scale of the relaxation of the smectic order, is much smaller than the twist penetration depth l t , confirmed by the agreement of previous theories based on the Frank free energy of monolayers with experiments 13,39,48 . Moreover, we assume a linear p-wall, so that the fields in equation (2) depend only on x.…”
Section: Methodssupporting
confidence: 64%
See 2 more Smart Citations
“…We assume that membranes and p-walls formed by filamentous fd viruses are type-II smectic materials, based on the analogy with superconductors 40,41 . In other words, the coherence length x, the length scale of the relaxation of the smectic order, is much smaller than the twist penetration depth l t , confirmed by the agreement of previous theories based on the Frank free energy of monolayers with experiments 13,39,48 . Moreover, we assume a linear p-wall, so that the fields in equation (2) depend only on x.…”
Section: Methodssupporting
confidence: 64%
“…Adding nonadsorbing polymer induces effective attractive interactions between otherwise electrostatically repulsive rods through the well-studied depletion mechanism 23 . Under specific conditions, the depleting agent condenses homogeneous rod-like viruses into colloidal membranes, one rod-length-thick chiral smectic-A (Sm-A*) monolayers of aligned rods whose continuum properties are identical to those of conventional lipid bilayers 13,14 . A feature that critically affects the coalescence pathways is the membrane's edge, consisting of a twisted layer of rods that penetrate a small distance into the membrane interior (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A beautiful series of experiments carried out by the Dogic group at Brandeis [7,8] demonstrated that filamentous viruses like fd-Y21M with half-length l f d = 430 nm or M13K07 with half-length l M13 = 560 nm form robust micron-scale monolayer membranes, depicted schematically in Fig. 3, when dispersed in water with a surfactant like dextran with a radius of a ≈ 25 nm, much less that the viral lengths.…”
Section: Membranes Of Filamentous Virusesmentioning
confidence: 99%
“…This article, based on my plenary lecture at ILCC 2016 will review recent work done at the University of Pennsylvania on two separate topics: chromonic liquid crystals in confined geometries [1][2][3][4], carried out mostly in Arjun Yodh's lab by Joonwoo Park and Zoey Davidson with some theoretical assistance from me and my student Louis Kang, and a theory, which is mostly the work of Louis Kang [5,6], for multi-micron-sized two-dimensional membranes composed of filamentous viruses stabilized by depletants studied in exquisite detail by Zvonimir Dogic and collaborators [7,8].…”
Section: Introductionmentioning
confidence: 99%